Strategi Pemasaran Mutu Terpadu (Total Quality Marketing) Dalam Lembaga Pendidikan Islam - Azis Nurul Iman; Barlian Fajri (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
Increasing educational marketing must be improved continuously and sustainably. TQM or Total Quality Marketing is a marketing strategy aimed at instilling quality awareness in all processes within an organization ,the method and type of data collection is library research, where books, journals and previous research results are collected that support the research topic, including literature about (TQM). Total Quality Marketing (TQM) in Islamic educational institutions is the main key to maintaining and improving the quality of educational services. The application of the TQM concept provides a solid foundation for maintaining customer satisfaction, especially in the context of Islamic education which places educational success as integral to the formation of students' character and morals.